'Embarrassing the State': The 'Ordinary' Prisoner Rights Movement in Ireland, 1972–6. (April 2020) - Wall, Oisín
This article explores the early years of the campaign for 'ordinary', not politically-aligned, prisoners' rights in Ireland. It argues that this campaign has often been overshadowed by the activities of 'political prisoners', who only constituted a small minority of prisoners in the period. The article follows the development and changing tactics of the ordinary prisoners' movement, through the rise and fall of the Prisoners' Union (PU) (1972–3) and into the early years of the Prisoners' Rights Organisation (PRO) (1973–6), which would become the longest-lasting and most vocal penal reform organisation in Ireland, until the formation of the Irish Penal Reform Trust in 1994. It argues that the movement constantly adapted its tactics to address emerging issues and opportunities. Ultimately, it contends that by 1976 the PRO was an increasingly legitimate voice in Ireland's public discourse on prisons. It shows that, although the campaign did not achieve any major penal reforms in this period, it had a significant impact on public debates about prisons, prisoners' mental health, the failures of the penal system, and prisoners' entitlement to human rights.